Inter- and intra-observer agreement of the motion palpation test for lumbar vertebral rotational asymmetry - Bracht M.A.* (2015)
© 2015, University of Toronto Press Inc.. All rights reserved.Purpose: To investigate inter- and intra-observer agreement in the assessment of lumbar vertebral rotational (VR) asymmetry by a motion palpation test. Methods: For this prospective and descriptive test–retest study, 51 asymptomatic participants (40 women, 11 men; mean age 23.3 [SD 5.6] years) were recruited from the community. Each participant was assessed in two sessions by the same three observers, who assessed VR by means of a palpatory test for movement asymmetry. This test is performed by applying posteroanterior pressure in an alternating manner to the left and right transverse processes of a vertebra to determine motion asymmetry in the transverse plane and thus the vertebral position. Observers classified the vertebral position as neutral, rotation to the right, and rotation to the left; they were blinded to which participant was being assessed and to any previous results. Results: Intra- and inter-observer agreement was verified by the kappa coefficient (k) and the weighted kappa coefficient (kw). Values of k and kw varied from 0.07 (95% CI, _0.10 to 0.245) to 0.37 (95% CI, 0.11–0.63) for intra-observer agreement and from 0.12 (95% CI, _0.06 to 0.29) to 0.30 (95% CI, 0.08–0.52) for inter-observer agreement. Conclusion: The motion palpation test used to assess VR asymmetry has low agreement levels; therefore, its clinical significance for measuring vertebral position is questionable.